2015
DOI: 10.1111/mmi.12990
|View full text |Cite
|
Sign up to set email alerts
|

Combining reverse genetics and nuclear magnetic resonance‐based metabolomics unravels trypanosome‐specific metabolic pathways

Abstract: SummaryNumerous eukaryotes have developed specific metabolic traits that are not present in extensively studied model organisms. For instance, the procyclic insect form of Trypanosoma brucei, a parasite responsible for sleeping sickness in its mammalianspecific bloodstream form, metabolizes glucose into excreted succinate and acetate through pathways with unique features. Succinate is primarily produced from glucose-derived phosphoenolpyruvate in peroxisome-like organelles, also known as glycosomes, by a solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 60 publications
4
34
0
Order By: Relevance
“…In a way, the life cycle of a pathogen is a series of irreversible differentiation steps, in which the cells adapt to a new environment to perform new functions. In addition, the use of modern metabolomics approaches has revealed that T. brucei uses an incomplete TCA cycle in PFs 53 and that proline has a different fate in PFs depending upon high- or low-glucose availability in the medium and has allowed the identification of the carbon and nitrogen sources of essential metabolites 5356 .…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…In a way, the life cycle of a pathogen is a series of irreversible differentiation steps, in which the cells adapt to a new environment to perform new functions. In addition, the use of modern metabolomics approaches has revealed that T. brucei uses an incomplete TCA cycle in PFs 53 and that proline has a different fate in PFs depending upon high- or low-glucose availability in the medium and has allowed the identification of the carbon and nitrogen sources of essential metabolites 5356 .…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…However, the trypanosomatid Krebs cycle does not function as a classical cycle. Pyruvate is converted mainly to acetate in a reaction linked with ATP synthesis (Tielens & van Hellemond, ; Bringaud et al, ). A similar reaction series has been described in a number of unicellular and multicellular species, but trypanosomatids are among the few species requiring oxygen (Müller et al, ).…”
Section: Euglenozoan Mitochondriamentioning
confidence: 99%
“…Metabolomics studies using different strategies have been essential to better understand trypanosome metabolism within the different hosts, including the important role of glycolysis and of glycolysis end‐products . As reviewed by Bringaud et al., different metabolomics approaches, such as nuclear magnetic resonance (NMR)‐based metabolomics, associated with alteration of the expression of genes of interest via knockout or RNAi, can be particularly useful for the characterization and understanding of metabolic pathways specific to T. brucei BSF or PCF.…”
Section: Omics and Parasite Biologymentioning
confidence: 99%